MENTAL DEVELOPMENT TRAINING FOR MILITARY SOLDIER AT ISKANDAR MUDA MILITARY COMMAND (A Theocentrical Humanism Approach) - Husein, Ahmad (Ar Raniry : International Journal of Islamic Studies, 2015)
This study aims to reveal the process of soldier's mental development in Iskandar Muda Military Command, both seen from the selection process to be soldier in educational institutions as well as in the unit assignment. This research is expected to find the development pattern in accordance with the challenging tasks for the National Military (TNI) ahead. By using a qualitative approach, this research has achieved several findings: 1) in the selection process, a soldier was just demanded to fundamentally have religious understanding without a standard point for depth understanding of religion, 2) in the first stage of education, the subject matter of religion only a broad outline of religious teachings, 3) religious activities is not part of military trainings curriculum, but it is merely education administrators’ policy, 4) the soldiers in unit deemed to have knowledge of the religion and an unwavering faith. Despite the fact that soldiers’ religious knowledge is still very low, while the faith is generally used as the symbolic emphasis that is less discussed. As a result, it is feared that mentality weakness when facing a tough task, both faced with the sophistication of tools, strategies and mental demands in modern warfare in the future.